2021
DOI: 10.3389/fpls.2021.787661
|View full text |Cite
|
Sign up to set email alerts
|

Insight Into the Multiple Branches Traits of a Mutant in Larix olgensis by Morphological, Cytological, and Transcriptional Analyses

Abstract: Larix olgensis is a tall deciduous tree species that has many applications in the wood fiber industry. Bud mutations are somatic mutations in plants and are considered an ideal material to identify and describe the molecular mechanism of plant mutation. However, the molecular regulatory mechanisms of bud mutations in L. olgensis remain unknown. In this study, dwarfed (or stunted), short-leaved, and multi-branched mutants of L. olgensis were found and utilized to identify crucial genes and regulatory networks c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
1
2
0
Order By: Relevance
“…Compared with MP, OP developed more branches at an early stage and the leaf axillary buds produced spiny spur shoots. Similar results have been reported in other species, such as birch and larch ( Han et al., 2019 ; Cai et al., 2021 ). In addition, the vascular bundles and abaxial epidermal cells of MP leaves were larger than those of OP, and the areal proportion of the pith, xylem, and phloem in new shoots of MP from the base to the tip was greater than that of OP, and almost no conducting tissue had differentiated at the shoot tip of OP.…”
Section: Discussionsupporting
confidence: 91%
“…Compared with MP, OP developed more branches at an early stage and the leaf axillary buds produced spiny spur shoots. Similar results have been reported in other species, such as birch and larch ( Han et al., 2019 ; Cai et al., 2021 ). In addition, the vascular bundles and abaxial epidermal cells of MP leaves were larger than those of OP, and the areal proportion of the pith, xylem, and phloem in new shoots of MP from the base to the tip was greater than that of OP, and almost no conducting tissue had differentiated at the shoot tip of OP.…”
Section: Discussionsupporting
confidence: 91%
“…The time, location, and level of gene expression are all directly regulated by TFs, which are important molecules in this process ( Cai et al., 2021 ). In this study, male and female cones were found to contain 2267 and 1227 genes related to these families of TFs, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Transcription factors (TFs) can read the genetic code by binding to cis-regulatory elements to activate or repress gene expression. TFs play a key role in plant development and gene expression regulation, forming complex gene regulatory networks [ 39 , 40 ]. To explore the TFs in response to shading in P. koraiensis , a total of 331 TF genes were identified as DEGs and encoded 68 TF families ( Supplementary Table S7 ).…”
Section: Resultsmentioning
confidence: 99%